Laminar Inflammation Responses in the Oligofructose Overload Induced Model of Bovine Laminitis - Ding, Jiafeng; Li, Shuaichen; Jiang, Lihong; Li, Yuepeng; Zhang, Xianhao; Song, Qiaozhi; Hayat, Muhammad A.; Zhang, Jian-Tao; Wang, Hongbin (Frontiers in Veterinary Science, 2020)
Laminitis causes significant economic loss and reduces animal welfare in global dairy farms. Inflammatory response plays an essential role in the sepsis-related laminar failure. No study has reported the inflammatory response in bovine laminitis-related oligofructose (OF)-overload model, which is relatively reliable and more similar to clinical cases. The aim was to determine the inflammatory response in the OF-induced bovine laminitis. A total of 12 Chinese Holstein dairy heifers (without claw disorder) were used in this study. The heifers were divided into two groups, including treatment (n=6) and control (n=6) groups. Each heifer of the treatment group was administered with an overloaded OF solution (17 g/kg of body weight) via a stomach tube. When both of 2-score lameness and consecutive positive reaction in the same claw were observed, the heifers were humanely euthanized. The heifers of the control group were also humanely euthanized at 72 h after administration of deionized water (2 L/100 kg of body weight). Real-time quantitative PCR (qPCR) was used to assess the laminar mRNA concentration of multiple inflammatory mediators in OF-treated heifers. The laminar mRNA concentration of IL-1β, IL-6, IL-8, CXCL-1, MCP-2, E-selectin, ICAM-1, COX-2, INOS-1 and PAI-1 was significantly increased (P<0.05) in the treatment group compared to control group. However, no significant difference was found for TNF-α, IL-10, CXCL-6 and MCP-1. Increased expression of multiple inflammatory mediators indicated the occurrence of the laminar inflammatory response at the early stages of the OF-induced bovine laminitis. The results suggest that inflammatory response may play an essential role in the pathogenesis of OF model of bovine laminitis.